Asmara urban history and development (L'architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2014)
This dissertation is a synthetic outcome of my doctoral thesis which focused on the urban history, development and continuous transformation of the city of Asmara in Eritrea, a country situated in the North Eastern point of Africa (Fig.1a). Asmara is defined by a strong Italian architectural expression. The thesis had been written with the aim to trace the story of the urban city of Asmara by retracing the different layers that have characterized the city in its history in order to determine its present pattern/configuration. The purpose was to trace, where possible, the origin of the present urban morphology, to identify the problems generated by both planned and unplanned urban space. The book in the first part discusses the urban development knowledge of Asmara before 1941, in a historical and logical discourse, using an analytical framework comprising the following components: population, geography and history of the place. However, the main focus of this study is the second part which connects the colonial development of the city with the contemporary form, from 1941 to 2005. During this period, various governments and administrations allowed for urban development, however, in an unplanned and non-integrated way. Published or documented evidence of the process of development of this period, could not be found during the research.